2018
DOI: 10.5114/pjr.2018.80301
|View full text |Cite
|
Sign up to set email alerts
|

Penile Doppler ultrasonography and elastography evaluation in patients with erectile dysfunction

Abstract: PurposeTo evaluate the relationship between erection grade, erectile function score, Doppler ultrasonography (US) indexes, and elasticity score (ES) according to Doppler US diagnosis in patients with erectile dysfunction (ED).Material and methodsReal-time strain type penile elastography was performed during penile Doppler US examination for 88 patients with ED. The diagnosis according to Doppler US was determined. Erection score according to the Erection Hardness Grading Scale was evaluated. A scoring for erec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 40 publications
0
24
1
1
Order By: Relevance
“…Erectile function was measured using the five-item version of the IIEF-5 and erection hardness grading scale (EHGS) (8). According to the scale, grades 0, 1, 2, 3 and 4 represent 'not enlarged', 'larger but not hard', 'hard but not hard enough for penetration', 'hard enough for penetration but not completely hard' and 'completely hard and fully rigid', respectively.…”
Section: Assessment Methodsmentioning
confidence: 99%
“…Erectile function was measured using the five-item version of the IIEF-5 and erection hardness grading scale (EHGS) (8). According to the scale, grades 0, 1, 2, 3 and 4 represent 'not enlarged', 'larger but not hard', 'hard but not hard enough for penetration', 'hard enough for penetration but not completely hard' and 'completely hard and fully rigid', respectively.…”
Section: Assessment Methodsmentioning
confidence: 99%
“… 31 showed that both the elasticity and the viscosity of the CC of the penis correlated with the peak systolic velocity and also viscosity and elasticity correlated negatively with future cardiovascular risk. Altinbas and Hamidi 32 performed real-time strain-type elastography during penile Doppler ultrasound examination in 88 patients with ED, and they were divided in agreement to Doppler ultrasound findings in normal, borderline for arterial insufficiency, arterial insufficiency and venous insufficiency. They found that when compared with the normal group, the arterial failure borderline group and the venous failure group had less stiffness, and the arterial failure group had higher stiffness than the normal group even though a statistically significant difference was recorded in the left CC in the venous failure group.…”
Section: Discussionmentioning
confidence: 99%
“…A PSV of <25 cm/s has been correlated with severe arterial disease on angiographic imaging. [ 8 ] Penile Doppler ultrasonography not only enables the arterial waveform to be analyzed but also allows for visualization of stenoses, damped waveforms and high-velocity that may occur as a result of a proximal stenosis elsewhere. Venous incompetence can cause ED through failure of cavernosal engorgement.…”
Section: Discussionmentioning
confidence: 99%